GREEN ACCOUNTING AND SUSTAINABLE PERFORMANCE OF SURAKARTA RESIDENCY GO-FOOD CULINARY MSMEs: MODERATING FINANCIAL PERFORMANCE - Kurniawati, Fransisca Roosiana; Widiyaningsih, Vitalis Ari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
Culinary SMEs in Surakarta experienced a 15% growth in 2023 (Arthur, Abanis, etc, 2013). SMEs have an environmental impact because they create waste. Economic development needs to be sustained. Sustainability consists of people, planet, and profit (Hidayat, 2020). (Rabbi, 2021)). Green accounting helps SMEs reduce their environmental footprint. Green accounting practices meet the demands of social responsibility and competitive advantage (Raydiant, 2021), (Agwu, 2014), (Naala, 2017). (Riduwan, 2018). Sustainabil- ity is influenced by financial performance (Giyanti, 2018), as seen from revenue and asset manage- ment (Agustina, 2014), (Maulita, 2020), (Nasir, 2015), (Aris, 2022) and (Clarkson, 2011). Sustainability is influenced by innovation, so the object of the research is MSMEs. The problem formulation is how the implementation of green accounting in Go-Food culinary MSMEs, and to determine whether financial performance affects business sustainability. The purpose of this research is to explore financial performance in mediating the influence of green accounting on sustainable performance in Go-Food culinary. The data collection method used in this research is the survey method. The data processing method involves observation, interviews, and litera- ture review. This research uses data analysis with SmartPLS software. The result of this study is that green accounting does not affect financial performance, green accounting does not affect sustainable performance, and financial performance positively affects per- formance sustainability. The implications of this research include that culinary SMEs need education on the importance of green accounting. Future researchers can explore the factors influencing the sustainability of culinary SMEs affiliated with Go-Food. Keywords: Green Accounting; Sustainable Performance; Culinary SMEs; Go-Food; Financial Performnace